Does Islamic Banking Performance Enhance Social Welfare? Evidence from Indonesia - Hapid Durohman; Fajar Andrian Sutisna; Danial Muhammad Wirdyansyah; Chetrine Alya Rinaima (Fakultas Ekonomi dan Bisnis Islam, 2024)
This study examines the influence of Islamic banking performance on social welfare in Indonesia, focusing on Shariah Non-compliance Risk (SNCR) and its relationship with the Capital Adequacy Ratio (CAR), unemployment, and Gross Domestic Product (GDP). SNCR occurs when Islamic banks fail to comply with Shariah principles, potentially leading to operational risks. Using panel data from 13 Islamic banks during 2017–2020, this research applies the Three-Stage Least Squares (3SLS) method to analyze the interaction between financial performance, macroeconomic indicators, and social welfare. Results show that higher CAR and unemployment tend to increase SNCR, while greater profitability, sufficient liquidity, and stable inflation help reduce it. Interestingly, although SNCR poses operational challenges, it has a positive impact on social welfare as reflected in GDP growth. This suggests that Islamic banks, despite Shariah compliance risks, still contribute to economic development. These findings emphasize the need for strong governance, effective risk control, and supportive economic policies. The study recommends that regulators enhance Shariah supervision and develop policies that strengthen financial stability while enabling Islamic banks to support national welfare goals. Overall, the research contributes to understanding how Islamic banking can balance financial soundness and social responsibility in the context of a growing Shariah-compliant financial system.